Impacto dos problemas bucais na qualidade de vida de pacientes vítimas de trauma facial - Alves, Carolina Pires [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Facial trauma is characterized by its emotional consequences, the possibility of persistent deformity if not treated properly and also by causing economic impact on the healthcare system. Currently, the literature contains several studies that assess the impact of oral health problems on quality of life in many clinical situations in dentistry. However, few studies have investigated this topic in victim patients of facial trauma. The objective of this project is to evaluate the impact of facial trauma in quality of life of traumatized patients. The study included patients seen by the service of Graduate and Maxillofacial Surgery, School of Dentistry, Araçatuba - Unesp who suffered facial bone fractures and were excluded patients with mental disability unable to adequately respond to the questionnaire. The impact of facial trauma on the quality of life of the population of this region was assessed by OHIP 14 instrument, which has been adapted to suit the situation. We interviewed 30 patients, each was interviewed three times. The first survey was done immediately after the diagnosis of trauma, the second 30 days after surgery and a third questionnaire after 90 days of surgery. The results showed a higher level of impact as soon as the maxillofacial trauma was diagnosed, and gradual decline along the course of treatment. It was observed that the facial trauma caused a moderate impact on the quality of life of patients who suffered facial trauma

O trauma facial é caracterizado por suas consequências emocionais, pela possibilidade de deformidade persistente quando não tratado adequadamente e também pelo impacto econômico que causa no sistema de saúde. Atualmente, a literatura apresenta diversos estudos que avaliam o impacto dos problemas de saúde bucal na qualidade de vida em diversas situações clínicas na odontologia. No entanto, poucos estudos investigam este tema em pacientes vítimas de trauma de face. O objetivo deste projeto é avaliar o impacto do trauma bucomaxilofacial na qualidade de vida de pacientes traumatizados. Participaram do estudo pacientes atendidos pelo serviço de Pós Graduação em Cirurgia e Traumatologia Bucomaxilofacial da Faculdade de Odontologia de Araçatuba - Unesp que sofreram fratura de ossos da face e foram excluídos pacientes com deficiência mental incapazes de responder adequadamente às perguntas do questionário. O impacto do Trauma de face na qualidade de vida da população dessa região foi avaliado por meio do instrumento OHIP 14, que foi adaptado para adequar-se à situação. Foram entrevistados 30 pacientes, sendo que cada um foi entrevistado em três momentos. O primeiro questionário foi feito imediatamente após o diagnóstico do trauma, o segundo após 30 dias da realização da cirurgia e um terceiro questionário após 90 dias da cirurgia. Os resultados mostraram maior nível de impacto assim que o trauma bucomaxilofacial foi diagnosticado, e gradativa queda ao transcorrer do tratamento. Observou-se que o trauma de face causou um impacto moderado à qualidade de vida do paciente vítima de trauma facial
Keywords: Qualidade de vida; Saúde bucal; Fraturas maxilomandibulares; Quality of life